Identification of NPR2 gene mutations affecting chondrocyte differentiation in short stature through JAK2-STAT5 - Shuoshuo Wei; Mingming He; Chuanpeng Zhang; Yanying Li; Mei Zhang; Xinguo Hou; Bo Ban; Qianqian Zhao (Orphanet Journal of Rare Diseases)
Abstract Background Natriuretic peptide receptor 2 (NPR2) is a crucial regulator of endochondral bone growth. However, patients carrying heterozygous NPR2 gene mutations exhibit a wide range of clinical phenotypes, and evidence regarding treatment efficacy is limited, with the pathogenic mechanisms not yet fully understood. Therefore, the aim of this study is to analyze and identify the clinical phenotypes, treatment outcomes, and pathogenic molecular mechanisms associated with NPR2 gene mutations. Methods Through exome sequencing, we sequenced NPR2 in three Chinese Han patients with short stature and validated the results in their families. Clinical characteristics, treatment follow-up analysis, protein 3D structure prediction, in vitro functional experiments, and transcriptome sequencing were used to examine the protein changes caused by the variants, their pathogenicity, and the underlying molecular mechanisms of the disease. Results All three patients with NPR2 (p.R318W, p.I908T, p.R976H) gene mutations exhibited non-specific skeletal dysplasia and short stature, with good efficacy of recombinant human growth hormone (rhGH) treatment. Compared to the wild type, the protein expression level of NPR2 mutants was significantly reduced (P < 0.001), and CNP-induced cyclic guanosine monophosphate (cGMP) production was significantly decreased (P < 0.0001). Transcriptome sequencing analysis revealed that Csf2 is a key differentially expressed gene between NPR2 mutant and wild type, and also an upstream regulator of the JAK2-STAT5 pathway. Further validation via qRT-PCR and Western blot showed that NPR2 gene mutations significantly reduced Csf2 gene mRNA expression (P < 0.05), and protein expression of JAK2, p-JAK2, and p-STAT5 was significantly decreased (P < 0.05). Further analysis revealed that NPR2 gene mutations significantly affected the expression of chondrocyte differentiation markers Sox9, Col2A1, and BMP4 (P < 0.001). Conclusion Our study provides new insights into the loss of function of NPR2. NPR2 gene mutations may influence the expression and phosphorylation levels of proteins in the JAK2-STAT5 signaling pathway by downregulating Csf2, thereby affecting chondrocyte differentiation and ultimately leading to short stature.